ROAD DAMAGED FACTOR ANALYSIS AT SIGNALIZED INTERSECTION (Case Study: The Traffic Light in Front of UNISSULA, Jl. Raya Kaligawe KM 4, Semarang) - Widya Ayu Prawesthi; Rachmat Mudiyono; Hermin Poedjiastoeti (UNISSULA Semarang, 2022)
Abstract: Road damage is common occurrence at signalized intersections. This causes delays in vehicle mobility and leads to congestion. This research seeks to investigate the types of damage occurring at signalized intersections, the factors causing the damage, and the alternatives to prevent the damage. Based on RCI method the value is 4,4, it means that on the location, the condition of the road are bad, many holes, and irregular surface. And also in the location often flooded, and affected by centrifugal force from the U turn, and the vibrating force while the vehicles waiting for the traffic light, and affected on the previous flexible layer get damaged. Based on that result, the repair possibility at the Traffic Light jalan Kaligawe KM. 4 (main road in front of Universitas Islam Sultan Agung) Semarang should use rigid pavement. And there are some specification items that relevant with the condition of the road: concrete slab thickness = 15cm, concrete slab length = 100m, shrink joint applied in space 5m, cross joint (dowel) applied with straight wire that have 32mm diameters, length 45cm, and space between the wire is 30cm, and tie bar use whorl beam that have 16mm diameters, length 70cm and space 75cm.